Orally-induced intestinal CD4+ CD25+ FoxP3+ treg controlled undesired responses towards oral antigens and effectively dampened food allergic reactions - Smaldini, Paola Lorena (2015)
The induction of peripheral tolerance may constitute a disease-modifying treatment for allergic patients. We studied how oral immunotherapy (OIT) with milk proteins controlled allergy in sensitized mice (cholera toxin plus milk proteins) upon exposure to the allergen. Symptoms were alleviated, skin test was negativized, serum specific IgE and IgG1 were abrogated, a substantial reduction in the secretion of IL-5 and IL-13 by antigen-stimulated spleen cells was observed, while IL-13 gene expression in jejunum was down-regulated, and IL-10 and TGF-β were increased. In addition, we observed an induction of CD4+ CD25+-FoxP3+ cells and IL-10- and TGF-β-producing regulatory T cells in the lamina propria. Finally, transfer experiments confirmed the central role of these cells in tolerance induction. We demonstrated that the oral administration of milk proteins pre- or post-sensitization controlled the Th2-immune response through the elicitation of mucosal IL-10- and TGF-β-producing Tregs that inhibited hypersensitivity symptoms and the allergic response.